“I Know How that Sounds and I Do Not Mean that as an, but I Mean Christ”: The Disturbance in the Symbolic Order in Dennis Kelly’s Theatre - Julien ALLIOT (E-REA)
According to Jacques Lacan, the “speakingbeing,” determined by the signifying chain, can only deal with words, names, never with the thing, and finds itself structured around an irreparable loss. In the wake of Beckett’s theatre, Dennis Kelly stages an original disturbance of the name, reduced to “debris,” in a fantasmatic and transgressive exploration of the condition of being an abandoned child (Orphans). In Kelly’s world, the standard syntax is subverted, the levels of usage of language (and languages themselves) are mixed, with constant interruptions (dislocations, aposiopeses, anacolutha...). On the contrary, what is brought to the fore is a sense of loss at the core of language, the representation of the inadequacy between signifier and signified. Using Lacanian concepts and topological tools to read Dennis Kelly’s works will allow us to question how and why the Imaginary takes over and proliferates, as if to approach the Real as closely as possible, without naming. Thus, the proliferation of television screens, as well as riveting, “in-yer-face” (according to the expression coined by Aleks Sierz) stage images, such as Michael’s father’s “cruxicide” in Debris, will be analysed in terms of their relation to the disturbance, disruption or disintegration of the Symbolic order.